Pengembangan Aplikasi Pengelolaan Infak dan Shodaqoh dengan Metode Rational Unified Process (RUP) pada Rumah Yatim Himmatul Ummah Al Islamiah di Kabupaten Kuningan - Nunu Nugraha; Rio Andriyat Krisdiawan; Heri Herwanto (FKOM UNIKU, 2024)
Himmatul Ummah Al Islamiah Orphanage in Kuningan Regency has a vital role in providing social assistance through the management of Infak and Shodaqoh. However, manual financial management presents challenges related to efficiency and transparency. Manual processes in managing Infak and Shodaqoh increase the risk of administrative errors, difficulty tracking funds, and lack of transparency in the distribution of donations. Therefore, technological innovation is needed to improve the effectiveness of financial management. This research aims to develop a web-based application that optimizes the Management of Infak and Shodaqoh in Orphanages, focusing on efficiency, transparency, and accountability. Application development is carried out by applying Rational Unified Process (RUP) as a structured system development method. Application design uses Unified Modeling Language (UML) to visually model the structure and functionality of the application. The results of the research are that the application developed has succeeded in increasing the efficiency of Infak and Shodaqoh management. The integration of RUP and UML ensures structured development and clear design, resulting in an easy-to-use, transparent, and accountable application. This research contributes positively to the effectiveness of Infak and Shodaqoh Management at Himmatul Ummah Al Islamiah Orphanage. The results can be used as a basis for similar charities to adopt similar technologies to improve the quality of financial management and donation distribution.